Sing to it [compact disc, unabridged] - Hempel, Amy (Simon & Schuster Audio, 2019)
From award-winning author Amy Hempel, one of the most celebrated and original voices in American short fiction: a stellar new story collection, and her first in over a decade, about people finding meaning and connection in the idiosyncratic lives they lead.